Fiscal regime and estimates of the underground economy in Malaysia: The currency demand approach in dynamic general equilbrium model - Eng, Yoke-Kee; Wong, Chin-Yoong (2007)
The purpose of present paper is to complement the conventional currency demand approach in the estimates of the size of underground economy by integrating it into a dynamic general equilibrium model. Our analysis demonstrated that it is not the current taxation burden that matters, but rather, it is the fiscal regime that affects both current and future taxation burdens that matters. Whether increasing current tax rates could have induced households to participate in underground activities depends on the path of government expenditure. Higher current tax rates along with a cut in government spending that signal a lower future tax burdens may indeed produce a smaller size of underground economy. On the flip side, lower current tax rates combined with increasing government spending that hint at greater future tax burdens could kick off a rising size of underground economy. We also uncover that the trend of the size of underground economy, after taking the fiscal condition into account, is in line with the existing literature on the role of underground economy as risk-sharing mechanism. After the adjustment for fiscal regime, we find that the size of underground economy in Malaysia, on general, is relatively smaller vis-a-vis the conventional measurement.